2017
DOI: 10.1159/000487000
|View full text |Cite
|
Sign up to set email alerts
|

A Paediatric Acute Promyelocytic Leukaemia Patient Harbouring a Cryptic <b><i>PML-RARA</i></b> Insertion due to a Complex Structural Chromosome 17 Rearrangement

Abstract: Acute promyelocytic leukaemia with PML-RARA fusion is usually associated with the t(15;17)(q24.1;q21.1) translocation but may also arise from complex or cryptic rearrangements. The fusion usually resides on chromosome 15 but occasionally on others. We describe a cryptic PML-RARA fusion within a novel chromosome 17 rearrangement. We performed interphase fluorescence in situ hybridisation (FISH) using a dual-fusion PML-RARA probe, followed by reverse transcriptase-polymerase chain reaction (RT-PCR) for PML-RARA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It reveals the diversity behavior of the p- and q-chromosomal arm signals. Recent FISH-based studies have shown that the reduced 5′RARA signal and the single PML-RARA fusion are located in the subterminal q-arm and p-arm regions of the rearranged chromosome 17, respectively (El-Hajj Ghaoui et al, 2017). Whether in a neoplastic disease or a non-cancerous disease, disease progression depends on the quantification and quality of the signal, and these signals differ between the p- and q-arms of each chromosome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It reveals the diversity behavior of the p- and q-chromosomal arm signals. Recent FISH-based studies have shown that the reduced 5′RARA signal and the single PML-RARA fusion are located in the subterminal q-arm and p-arm regions of the rearranged chromosome 17, respectively (El-Hajj Ghaoui et al, 2017). Whether in a neoplastic disease or a non-cancerous disease, disease progression depends on the quantification and quality of the signal, and these signals differ between the p- and q-arms of each chromosome.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Wu et al (2010) found that 16 patients with growth stunting or mental retardation had several deletions at 14 different subtelomeric regions (1p, 2p, 4p, 6p, 7p, 7q, 8p, 9p, 10p, 11q, 14q, 15q, 16p, and 22q) and repeats at seven subtelomeric regions (3q, 4p, 6q, 7p, 8p, 12p and 22q). What’s more, subtelomeric rearrangements are also the major cause of idiopathic mental retardation, growth stunting or retardation, and malignant blood system diseases (Ravnan et al, 2006; Tos et al, 2013; El-Hajj Ghaoui et al, 2017).…”
Section: Subtelomeres and Subtelomeric Dna Methylationmentioning
confidence: 99%
“…The upstream part was inserted into chromosome X, whereas the downstream part was inserted into the TBL1XR1 locus. [6][7][8][9][10] Welch et al 11 demonstrated that WGS is useful for detection of PML-RARA in masked cases. The transcript of the chimeric gene, TBL1XR1-RARA, was confirmed as an inframe fusion by RT-PCR, which was identical to that of the previously reported cases ( Figure 2B).…”
Section: Case Reportmentioning
confidence: 99%
“…The same situation has been reported in cases with PML-RARA-positive APL. [6][7][8][9][10] Welch et al 11 demonstrated that WGS is useful for detection of PML-RARA in masked cases.…”
Section: Case Reportmentioning
confidence: 99%